Selection of optimum cutting condition of cobalt-based superalloy with GONNS - (:unkn) unknown (SPRINGER LONDON LTD, 2010)
Machining of new superalloys is challenging. Automated software environments for determining the optimal cutting conditions after reviewing a set of experimental results are very beneficial to obtain the desired surface quality and to use the machine tools effectively. The genetically optimized neural network system (GONNS) is proposed for the selection of optimal cutting conditions from the experimental data with minimal operator involvement. Genetic algorithm (GA) obtains the optimal operational condition by using the neural networks. A feed-forward backpropagation-type neural network was trained to represent the relationship between surface roughness, cutting force, and machining parameters of face-milling operation. Training data were collected at the symmetric and asymmetric milling operations by using different cutting speeds (V-c), feed rates (f), and depth of cuts (a(p)) without using coolant. The surface roughness (Ra-asymt, Ra-symt) and cutting force (Fx(asymt), Fy(asymt), Fz(asymt), Fx(symt), Fy(symt), Fz(symt)) were measured for each cutting condition. The surface roughness estimation accuracy of the neural network was better for the asymmetric milling operation with 0.4% and 5% for training and testing data, respectively. For the symmetric milling operations, slightly higher estimation errors were observed around 0.5% and 7% for the training and testing. One parameter was optimized by using the GONNS while all the other parameters, including the cutting forces and the surface roughness, were kept in the desired range.
Keywords: Surface roughness; Cutting forces; Surface milling; Stellite 6; CNC milling; Artificial neural networks; GONN; Genetic algorithm; SURFACE-ROUGHNESS; OPERATING-CONDITIONS; GENETIC ALGORITHMS; TOOL WEAR; OPTIMIZATION; MICROSTRUCTURE; PERFORMANCE; QUALITY